Basics of blast resilient design of concrete frame buidlings - Khan, Zafar Ahmad (Knovel, 2011)
In this article the author will explain the nature of blast forces and their effects on buildings, in a straightforward manner. He will also clarify the difference between blast resistance and blast resilience. Various measures to improve blast resilience in buildings will be described, with the intent that an experienced architect or structural engineer can make informed decisions in the early stages of planning and design.